If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(X + -6) + 5 = 8 Reorder the terms: 3(-6 + X) + 5 = 8 (-6 * 3 + X * 3) + 5 = 8 (-18 + 3X) + 5 = 8 Reorder the terms: -18 + 5 + 3X = 8 Combine like terms: -18 + 5 = -13 -13 + 3X = 8 Solving -13 + 3X = 8 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 3X = 8 + 13 Combine like terms: -13 + 13 = 0 0 + 3X = 8 + 13 3X = 8 + 13 Combine like terms: 8 + 13 = 21 3X = 21 Divide each side by '3'. X = 7 Simplifying X = 7
| 2x+8x-3x-7x= | | -b+6b=b+1+5b | | -3t+16=10 | | f(x)=5x^4+15x^2+10 | | 79+k=84 | | 9x+x=70+8x | | 7=5v-3 | | -15(x-c)=15 | | N^2+20n-40=-9 | | -3+16=10 | | y-1=-6(x+2) | | 9a+5b=1 | | x+2x+2(2x)+2(4x)=64 | | 55+165x=1540 | | B^2+16b-15=2 | | 5y-14=4 | | 5-y+3y=3-3y+3y | | 25x^2+25x-2500=0 | | H(t)=86+13t-4.9t^2 | | X^2+20+51=0 | | Z^2+i=1 | | 0=2x^2-8x+6 | | 5x+16=-18x+38 | | A^2-12a-62=0 | | x-104=64 | | (6x-5)(4x+8)=0 | | 2.5(2x+4)=30 | | 5(3x-8)-2=-33-15x | | 2b^2=-6 | | 9x^2+16=25 | | x+18x=3 | | 5(3x-8)-2=-33-15v |